Free Float and Corporate Market Value: A Study of 2001-2010 Period - Caixe, Daniel Ferreira; Matias, Alberto Borges; Borges de Oliveira, Sonia Valle Walter (Organizações & Sociedade, 2014)
In Brazil, in general, ownership structure of companies is characterized by its high concentration. In this situation, the role of corporate governance model is no longer resolving the agency conflict between managers and shareholders, but represent the mitigation of clash of interests between controlling and minority shareholders. In academic literature, there is still no consensus on the relationship between ownership and control structure and corporate performance. Thus, this study aimed to determine if the free float has impacted on corporate market value in Brazil, over the years of 2001 to 2010. For this purpose, a sample of 236 Brazilian non-financial publicly traded companies was used, counting 1190 observations. Dynamic models of multiple linear regression were employed, estimated by System Generalized Method of Moments (GMM-Sys). The results indicated that total free float was not associated with dependent variables. However, the percentage of voting shares outstanding available for trading in the market had a positive impact on Tobin’s Q and Firm Value over Total Assets.